A utilização do aplicativo Geogebra para smartphone como recurso didático nas aulas de matemática do Ensino Fundamental São Luís - SILVA, Elanny Roma Pereira da (2018)
Faced with a society that is constantly changing due to advances in it is important to investigate, discuss ideas and establish strategies that reflect future improvements in education in order to use them as a didactic resource, especially with regard to mobile digital media that already occupy school spaces. At the outset, a historical survey of the development of some technologies and their influence on the social environment, and how these technologies evolved within public schools, is carried out. Next, we develop a deepening of the concept of M-learning, which refers to the use of mobile devices for learning, and a brief tutorial of the application Geogebra Graphing Calculator with version for smartphones. Finally, the methodology of the work and the results obtained through a research carried out with two focuses: to ascertain the profile of the teachers regarding the use of the computer and smartphones; the prospect students of a public school who have carried out activities with the Geogebra app. The results show that smartphone devices have gained space within schools and that can be used as a resource for learning, as long as accompanied by the teacher based on strategic planning.